An internet of things-based pump and aerator control system - Mawardi Mawardi; Panangian Mahadi Sihombing; Nabila Yudisha (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
Small-scale shrimp farmers in Hamparan Perak District, Deli Serdang Regency, Indonesia, conduct direct water quality supervision and manually use aerators and water pumps. Thus, it is inefficient in meeting the water quality required for shrimp farming and using production costs. This study aims to test the performance of an internet of things (IoT)-based prototype in supervising and controlling the aerator and pump in a shrimp pond. This prototype comprises an ESP32, three sensors: the DS18B20 sensor, MLX90614 sensor, and JSN-SR04T sensor, and two relays to control the aerator and pump automatically. Prototype testing is done directly on shrimp ponds by placing the prototype in an electrical panel connected to a power circuit. Based on the study's results, it is known that the prototype can measure water temperature. The water level and temperature of the aerator motor are pretty accurate. In addition, the prototype can also control the aerator and water pump well and send notifications to users automatically via smartphones.